Pelatihan Menulis dengan Pendekatan Talk For Writing Bagi Guru Bahasa Inggris - Sri Kusuma Ningsih (Jurnal Abdimas Adpi Sosial dan Humaniora, 2023)
The quality of students’ writing English is the reason for conducting Talk for Writing (TfW) workshop. This workshop aims to provide insight into how to teach writing in an interesting and fun way. English teachers in Merauke, South Papua, are the main targets for this activity, considering that teachers in this location rarely get refreshments for English teaching strategy. The method to implement this activity is carried out offline through several stages and namely, the lecture method used to introduce the concept of TfW. The second stage is a demonstration method showing a work process or stage of making a magpie that will be used in the TfW process. The third stage is the practice method. At this stage, the participants practiced creating a magpie and writing using the TfW approach. The final stage was an evaluation where the teachers received feedback based on the magpie and the writing they had made. During the workshop, the enthusiasm of the participants was very high. In addition, the knowledge and understanding of the use of TfW techniques have increased.